Iceland : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in Iceland during 1990-96. It analyzes the origins of the current economic expansion associated with a swing in the current account and in emerging inflation pressure. Three driving forces are emphasized: the positive supply shock affecting the fisheries; the expansion of the power intensive industry; and brisk increases in real wages over the past two years (1995-96). The paper highlights that the main sources of upside risks comprise the likely construction of a new aluminum smelter.